Genetic Polymorphisms In The Phase I And Phase II Xenobiotic Metabolizing Enzymes In Malaysian Population And Their Influence On Colorectal Cancer Susceptibility - Shahpudin, Siti Nurfatimah Mohd (2012)
Sporadic Colorectal Cancer (CRC) is a multifactorial disease and factors contributing to its etiopathogenesis include dietary and lifestyle habits on one hand and genetic predisposition on the other hand. Exposure to environmental carcinogens through dietary components and cigarette smoke are associated with an increased risk of CRC. However, the genetic predisposition factors associated with CRC development largely remain undetermined. It was hypothesized that genetic variations in xenobiotic metabolism genes may play a role in how individuals will respond to carcinogenic compounds and hence affect the risk of developing CRC. So, this case-control study which involved 566 study subjects (255 histopathologically confirmed sporadic CRC patients and 311 normal healthy controls) was designed and undertaken at Human Genome Centre, University Sains Malaysia during the period 2009-2011, to investigate the influence of genetic polymorphisms of few xenobiotic metabolizing genes in CRC susceptibility risk. Ten polymorphisms from 6 genes encoding enzymes involved in xenobiotic metabolism (GSTT1, GSTM1, GSTP1 Ile105Val, CYP1A2 G3860A, CYP1A2 T739G, CYP1A2 C729T, NAT1 C1095A, NAT2 G191A, NAT2 A803G, NAT2 G857A) were selected as candidate SNPs to determine their influence, either singly or as combination genotypes, in CRC susceptibility risk and with the ultimate aim of identifying putatively protective and/or at risk genotypes.